Analisis Pembiayaan Modal Kerja Syariah dalam Mendukung Strategi Pengembangan Usaha oleh Bank Syariah Indonesia - Mirnawati Mirnawati; Ismail Keri; Shadriyah Shadriyah (AKUNTANSI 45, 2025)
This study aims to analyze the role of sharia-based working capital financing in supporting business development strategies at Bank Syariah Indonesia KCP Watampone. The research method used in this study is quantitative with a survey approach. Data were collected through questionnaires distributed to customers who received sharia-based working capital financing. Data analysis was conducted using descriptive and inferential statistical techniques to test the proposed hypotheses. The results of the study indicate a positive and significant influence between sharia-based working capital financing on business development, where customers who utilize this financing experience increased productivity and business growth. These findings indicate that sharia-based working capital financing can be an effective tool in supporting business development strategies. This research is expected to provide insights for banks in formulating better policies related to sharia-based financing products